Reel of Fortune : a Miss Fortune Mystery, Book 12 - DeLeon, Jana (DeLeon, Jana. Miss Fortune series., 2018)
Nothing says Welcome Home like a murder. It's official. Fortune Redding is out of the CIA and a newly minted resident of Sinful, Louisiana. She never expected her homecoming to be all apple pie and hugs, but a murder wasn't on her list of things to deal with before she'd even gotten her name stenciled on her mailbox. Boone Carre-- Hooch, to the locals-- was a drunk and a louse and had shafted pretty much everyone he'd ever done business with. So when someone kills him, there is no shortage of suspects. Unfortunately, Ally is at the top of the list. Fortune, Ida Belle, and Gertie know that Ally isn't capable of murdering anyone, but with an ambitious ADA looking to make a name for himself, and the local gossip train intent on finding someone to blame, they know they have to find the killer and clear Ally's name.